2016
DOI: 10.1123/jab.2014-0243
|View full text |Cite
|
Sign up to set email alerts
|

Quadrupedal Locomotion–Respiration Entrainment and Metabolic Economy in Cross-Country Skiers

Abstract: A 1:1 locomotion-respiration entrainment is observed in galloping quadrupeds, and is thought to improve running economy. However, this has not been tested directly in animals, as animals cannot voluntarily disrupt this entrainment. The purpose of this study was to evaluate metabolic economy in a human gait involving all four limbs, cross-country skiing, in natural entrainment and forced nonentrainment. Nine elite cross-country skiers roller skied at constant speed using the 2-skate technique. In the first and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
2
6
0
1
Order By: Relevance
“…We interpret this finding to suggest that the relative orientation of the tibiotalar and subtalar axes of rotation may be more important than the individual orientation of either axis. This is in agreement with previous studies that have demonstrated that the skew angle, which quantifies the relative orientation between two axes of rotation, is a functionally important parameter in complex multi-degree-off-reedom joints, such as the carpometacarpal joint of the thumb, 5 the radiocarpal and midcarpal joints of the wrist, 22 and tibiotalar and subtalar joints of the ankle. 26 This functional importance results from the interdependence of these joints' degrees-off-reedom during typical activities of daily living.…”
Section: Discussionsupporting
confidence: 93%
“…We interpret this finding to suggest that the relative orientation of the tibiotalar and subtalar axes of rotation may be more important than the individual orientation of either axis. This is in agreement with previous studies that have demonstrated that the skew angle, which quantifies the relative orientation between two axes of rotation, is a functionally important parameter in complex multi-degree-off-reedom joints, such as the carpometacarpal joint of the thumb, 5 the radiocarpal and midcarpal joints of the wrist, 22 and tibiotalar and subtalar joints of the ankle. 26 This functional importance results from the interdependence of these joints' degrees-off-reedom during typical activities of daily living.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, a decrement in kicking velocity was correlated with the increment in a shuttle-running test from the second lactate threshold [12]. Yet, a decrement in a fatigue protocol based on countermovement jumps did not establish correlations with the decrement in the maximal kicking velocity [14].…”
Section: Introductionmentioning
confidence: 81%
“…Maximal ball velocity and accuracy have been the most studied variables related to the kicking action, with studies on the effects of diverse exercise protocols in both factors [5], such as match simulations [5], circuits [6][7][8][9], running on a treadmill at different intensities [10,11], incremental tests [12], squats [13], countermovement jumps [14], knee flexion and extension [15] and the real competition [16]. Therefore, a large number of fatigue protocols are found, which makes it difficult to interpret the results of this concerning the kick and the capacity to generate fatigue; in some cases, the physiological demands of the game are not faithfully reproduced [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, body segment inertial parameters (BSIPs) (which are: mass, center of mass (COM), and inertia tensor) have been shown to be highly important for clinical and biomechanical research [1,2]. They allow monitoring the variations in muscle-mass in patients during hospitalization, rehabilitation, or neurological examination [3] and are of crucial importance for biomechanical analyses such as inverse dynamics computations [46], in particular for gait analyses.…”
Section: Introductionmentioning
confidence: 99%